Assembling the genome of the African wild rice Oryza longistaminata by exploiting synteny in closely related Oryza species. (December 2018) - Reuscher, Stefan; Furuta, Tomoyuki; Bessho-Uehara, Kanako; Cosi, Michele; Jena, Kshirod; Toyoda, Atsushi; Fujiyama, Asao; Kurata, Nori; Ashikari, Motoyuki
Abstract The African wild rice speciesOryza longistaminata has several beneficial traits compared to cultivated rice species, such as resistance to biotic stresses, clonal propagation via rhizomes, and increased biomass production. To facilitate breeding efforts and functional genomics studies, we de-novo assembled a high-quality, haploid-phased genome. Here, we present our assembly, with a total length of 351 Mb, of which 92.2% was anchored onto 12 chromosomes. We detected 34, 389 genes and 38.1% of the genome consisted of repetitive content. We validated our assembly by a comparative linkage analysis and by examining well-characterized gene families. This genome assembly will be a useful resource to exploit beneficial alleles found inO. longistaminata . Our results also show that it is possible to generate a high-quality, functionally complete rice genome assembly from moderate SMRT read coverage by exploiting synteny in a closely relatedOryza species. Stefan Reuscher et al. assembled the genome of an African wild rice species to facilitate breeding efforts and functional genomic studies. They used SMRT sequencing, chromosomal synteny between rice species, and a linkage map to assemble the 351 Mb genome into 12 chromosomes.